TWO-WAY COMMUNICATION AND DIGITAL TALENT EMPOWERMENT: ANALYSIS OF TELKOMSEL'S CSR PROGRAM AT RUMAH BUMN YOGYAKARTA - Dyas Dwi Azhar Rumeksa; Lukman Hakim (SOSIOEDUKASI, 2026)
This study analyzes PT Telkomsel's CSR program in developing the digital competency of the younger generation at Rumah BUMN Yogyakarta from a corporate communication perspective. Using a qualitative case study involving 10 informants (4 companies, 6 participants), data was collected through semi-structured interviews, observations, and document analysis using the Braun & Clarke thematic method. The findings indicate that Telkomsel's CSR program functions as a symmetrical two-way communication that not only transfers technical skills in digital literacy and entrepreneurship but also facilitates the empowerment process by increasing participants' self-confidence, communication skills, and entrepreneurial mindset. The communication dynamics between facilitators and participants demonstrate a dialogic, participatory approach, where participants are empowered through active participation and the construction of shared meaning. From the company's perspective, this program contributes to the construction of a corporate identity as an institution concerned with sustainable social development, not merely philanthropy or image building. The study concludes that CSR has the potential to be a transformative corporate communication instrument if designed with the principle of sustainable empowerment. This is an open access article under the CC–BY-SA license.